2022
DOI: 10.3389/fpsyg.2022.838835
|View full text |Cite
|
Sign up to set email alerts
|

The Future Looks Good: Examining the Associations Between Coping, Psychological Distress, and Optimism

Abstract: The recent pandemic and consequent lockdown had a substantial impact on mental health and optimism regarding the future. Previous research showed that levels of depression, anxiety, and stress had increased throughout the pandemic. Nonetheless, how individuals cope when faced with adversity may be associated with positive expectations regarding the future. A sample of 274 Portuguese workers (female = 54) with a mean age of 40.86 (SD = 0.70) and work experience of 19.68 years (SD = 12.07) met inclusion criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…This suggests that increased levels of depressive symptoms are associated with a decreased perception of satisfaction with life. Santos et al [25] also found similar results, indicating that workers with higher levels of depressive symptoms and stress exhibit lower levels of optimism regarding the future, which is an indicator of well-being. The association between symptoms of depression, anxiety, and stress with life satisfaction can be understood through theoretical frameworks that emphasize the impact of mental distress on subjective well-being.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…This suggests that increased levels of depressive symptoms are associated with a decreased perception of satisfaction with life. Santos et al [25] also found similar results, indicating that workers with higher levels of depressive symptoms and stress exhibit lower levels of optimism regarding the future, which is an indicator of well-being. The association between symptoms of depression, anxiety, and stress with life satisfaction can be understood through theoretical frameworks that emphasize the impact of mental distress on subjective well-being.…”
Section: Discussionmentioning
confidence: 68%
“…By examining the relationship between each coping strategy, psychological distress, and life satisfaction, this study will contribute to the existing literature in health psychology [5,27,28]. Previous studies conducted among workers have typically treated coping strategies as a unifying construct rather than considering them as multiple dimensions of mental health [25]. Based on this rationale, we propose the following hypotheses: Hypothesis 1 (H1).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This issue seems to be common for individuals with mental disorders, such as people with schizophrenia, depression and/or anxiety. These individuals have demonstrated a shared pattern of difficulties when relating and responding to emotional distress [12], characterized by an increased tendency to engage with maladaptive strategies, such as behavioral disengagement, denial, self-distraction, and self-blame [13], which have been associwww.jpublichealth.org ated with emotional eating. This process, known as emotional eating, serves as a tangible manifestation of the intricate interplay between emotions and dietary choices.…”
Section: Emotional Eating and Its Contribution To Disordered Eating P...mentioning
confidence: 99%
“…Currently, there are highly stressful events that generate mental health problems in the world and national population, related to a high incidence of stress, anxiety, depression, decreased optimism (Santos et al, 2022), negative psychological impact (Brooks et al, 2020) and overflow in the capacity to respond to stress (Guillén-Díaz et al, 2021). In complex situations of such magnitude, coping with stress provides evidence of how people act to a stressful event.…”
Section: Introductionmentioning
confidence: 99%